Second language retention: Language use as a contributing factor. - Ducharme, Daphne Ann. (University of Ottawa (Canada), 1995)
Using data collected by Wesche (1992), this study examines the effect of the use of French as a second language on the performance of subjects in receptive skills (listening and reading comprehension) and productive skills (speaking and writing). Language use is presented as one of three major factors (together with the initial level of proficiency, and the role of motivation) reported from earlier research (Harley, 1994) as relevant to the maintenance of language skills. Results of earlier investigations (Bahrick, 1984; Clark & Jorden, 1984) have already shown that the level of proficiency may influence long-term retention of knowledge. Similarly, the role of motivation has been studied extensively by a number of researchers (Gardner, 1982; Gardner, Lalonde and MacPherson, 1985; Gardner, Lalonde, Moorcroft and Evers, 1985; Gardner, Moorcroft and Metford, 1989; Gardner and Lysynchuk, 1990) and it is now generally accepted that attitudes affect motivation which in turn influences the long-term retention of learned material (Moorcroft and Gardner, 1987). Just as motivation is seen as a crucial component in language learning, it stands to reason that to maintain a level of performance, it is important to benefit from a supportive external environment (Edwards, 1977). The more practice is available to subjects who wish to maintain their skills, it seems, the more likely they are to be successful in doing so. This research attempts to establish a relationship between the use of the language after learning has occurred and the difference between pre and post test measures using the data collected by Wesche (1992). A number of specific independent variables will be examined, specifically the number of university courses taken in French, the number of books read in French, the number of movies seen in French, the number of hours of television watched in French, and the number of other activities in French.
Keywords: Education, Language and Literature.